Komunikasi Virtual Cyberbullying Melalui Perilaku Trash Talking Pada Pemain Game Online Valorant - Maulana Ihsan Zarkasih; Nurul Mustaqimmah (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
Trash talking, as a form of cyberbullying, is often found in internet gaming cafes such as White Wolf Arena and refers to harmful actions such as insinuating, insulting or verbally abusing other players. This phenomenon occurs through voice or text messaging features in anonymous virtual communication, triggering negative behaviours such as trolling and AFK. The vocabulary of Trash talking includes animal words, adjectives, objects, conditions, and human organs. This study aims to analyse the Trash talking behaviour of Valorant players using a descriptive qualitative method with seven purposively selected informants. Data were collected through interviews, observation, and documentation, and analysed using the Miles and Huberman technique with data triangulation. The results showed that Trash talking behaviour is influenced by sociopsychological and situational factors. The communication media used include voice chat, text chat, and stickers, where the detection system is more effective on text. Virtual communication showed varied Trash talking vocabulary and different levels of offensiveness between voice chat and text. This research identified behaviour, media and virtual communication as the main aspects of Trash talking in Valorant.